Galactosamine-Conjugating Zwitterionic Block Copolymer for Reduction-Responsive Release and Active Targeted Delivery of Doxorubicin to Hepatic Carcinoma Cells. (20th April 2020) - Zhai, Jingming; Zhou, Biyu; An, Yanhui; Lu, Binzhong; Fan, Yonggang; Li, Junbo
Abstract : Nanocarriers with integrated advantage, such as excellent stealth property, active targeting function, and rapid intracellular drug release, are significant for cancer treatment. Herein, a biodegradable zwitterionic triblock copolymer containing disulfide-linked poly- ε -caprolactone and polycarboxybetaine methacrylate (PCB-SS-PCL-SS-PCB) was first synthesized and then partly modified with galactosamine (GAL) for constructing polymeric micelle drug carrier with multifunctionality. Polymeric micelles showed ultralow protein absorption in serum and obvious reduction-responsiveness in the presence of glutathione, provided by the zwitterionic polymer shell and the disulfide bond, respectively. Furthermore, active targeting of the carrier to hepatic carcinoma cells was achieved via GAL ligands on PCB shells due to their specific binding to asialoglycoprotein receptors on the cell surface. As expected, in vivo competition studies demonstrated that doxorubicin- (DOX-) loaded GAL-modified micelles have better anticancer effect in hepatic tumor-bearing mice than free DOX and nontargetable micelles. As a result, this novel multifunctional carrier provides a valuable strategy to design promising anticancer drug delivery systems for liver cancer treatment.